2017
DOI: 10.12688/f1000research.12064.1
|View full text |Cite
|
Sign up to set email alerts
|

A GAP that Divides

Abstract: Cytokinesis in metazoan cells is mediated by an actomyosin-based contractile ring that assembles in response to activation of the small GTPase RhoA. The guanine nucleotide exchange factor that activates RhoA during cytokinesis, ECT-2, is highly regulated. In most metazoan cells, with the notable exception of the early Caenorhabditis elegans embryo, RhoA activation and furrow ingression require the centralspindlin complex. This exception is due to the existence of a parallel pathway for RhoA activation in C. e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…Another model proposes that its GAP activity is required during cytokinesis to turn off the GTPase Rac1. We recently elaborated on the merits of these models in a separate review [69]. A major concern with the latter model is that the experiments to support it have been performed in the presence of a parallel RhoA activation pathway peculiar to C. elegans (see NOP-1 section).…”
Section: Structure and Function Of Cyk4mentioning
confidence: 99%
“…Another model proposes that its GAP activity is required during cytokinesis to turn off the GTPase Rac1. We recently elaborated on the merits of these models in a separate review [69]. A major concern with the latter model is that the experiments to support it have been performed in the presence of a parallel RhoA activation pathway peculiar to C. elegans (see NOP-1 section).…”
Section: Structure and Function Of Cyk4mentioning
confidence: 99%
“…However, RacGAP exhibits preferential GAP activity toward Rac and Cdc42 rather than Rho in vitro ( Toure et al, 1998 ; Bastos et al, 2012 ; Jantsch-Plunger et al, 2000 ). Genetic experiments in C. elegans embryos have led to conflicting models (discussed in Basant and Glotzer, 2017 ) in which the CYK4 GAP domain either targets Rac ( Canman et al, 2008 ; Zhuravlev et al, 2017 ), or acts non-canonically to activate Rho ( Loria et al, 2012 ; Zhang and Glotzer, 2015 ). Another candidate GAP for Rho inactivation at the CR is p190RhoGAP-A/ARHGAP35 ( Mikawa et al, 2008 ; Su et al, 2009 ; Manukyan et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with a role in activating RhoA, CYK-4 orthologs have been shown to bind ECT-2 via a region in their N-terminal half, positioned between the coiled-coil and C1 domains, and this binding is proposed to relieve autoinhibition of ECT-2 to activate RhoA for contractile ring assembly (Somers and Saint 2003;Yüce et al 2005;Burkard et al 2009;Wolfe et al 2009;Loria et al 2012;Zhang and Glotzer 2015;Basant and Glotzer 2017). It is surprising that a GAP domain, expected to inactivate small GTPases by stimulating their GTP hydrolysis activity, acts to promote RhoA signaling (Basant and Glotzer 2017). Recent work has shown that mutations that specifically disrupt the Rho GTPase binding interface of the GAP domain compromise RhoA activation during cytokinesis (Zhang and Glotzer 2015).…”
Section: Centralspindlin and Cytokinesis: The Role Of The Cyk-4 Gap Dmentioning
confidence: 92%
“…Across systems, including C. elegans, there is good evidence that CYK-4 homologs play a role in the local activation of the small GTPase RhoA to promote contractile ring assembly (Motegi et al 2006;Loria et al 2012;Zhang and Glotzer 2015;Basant and Glotzer 2018). Consistent with a role in activating RhoA, CYK-4 orthologs have been shown to bind ECT-2 via a region in their N-terminal half, positioned between the coiled-coil and C1 domains, and this binding is proposed to relieve autoinhibition of ECT-2 to activate RhoA for contractile ring assembly (Somers and Saint 2003;Yüce et al 2005;Burkard et al 2009;Wolfe et al 2009;Loria et al 2012;Zhang and Glotzer 2015;Basant and Glotzer 2017). It is surprising that a GAP domain, expected to inactivate small GTPases by stimulating their GTP hydrolysis activity, acts to promote RhoA signaling (Basant and Glotzer 2017).…”
Section: Centralspindlin and Cytokinesis: The Role Of The Cyk-4 Gap Dmentioning
confidence: 96%
See 1 more Smart Citation